Cost-effectiveness of trifluridine/tipiracil as a third-line treatment of metastatic gastric cancer, including adenocarcinoma of the gastrohesophageal junction, among patients previously treated in Greece. (17th February 2022) - Gourzoulidis, George; Koulentaki, Maria; Koumarianou, Anna; Samadas, Epaminondas; Androulakis, Nikolaos; Xynogalos, Spyridon; Papakotoulas, Pavlos; Boukovinas, Ioannis; Karamouzis, Michalis; Souglakos, John; Chotzagiannoglou, Vasiliki; Beletsi, Alexandra; et al.
ABSTRACT: Objective: To evaluate the cost-effectiveness of trifluridine/tipiracil (FTD/TPI) compared with best supportive care (BSC) for the treatment of patients with metastatic gastric cancer(mGC), including gastroesophageal junction adenocarcinoma(GEJ), who have received at least two prior therapies for metastatic disease and are eligible for third-line treatment, in Greece. Methods: A partitioned survival model was locally adapted from a public payer perspective over a 10-year time horizon. Clinical, safety and utility data were extracted from literature. Resource consumption data obtained from a panel of local experts using a questionnaire developed for the study was combined with unit costs obtained from official sources. All costs reflect the year 2020 (€). Outcomes of the model were patients' life years (LYs) and quality-adjusted life years (QALYs), total costs and incremental cost-effectiveness ratio (ICER) per QALY and LY gained. Results: The total cost per patient was estimated to be €6, 965 for FTD/TPI and €1, 906 for BSC, while FTD/TPI was associated with 0.180 and 0.107 increments in LYs and QALYs, respectively, compared with BSC, resulting in an ICER of €47, 144 per QALY gained and €28, 112 per LY gained. Conclusion: FTD/TPI was estimated to be a cost-effective treatment option for eligible third line mGC patients, including GEJ in Greece.